Exploring factors that prevent non-compliance with Basic Conditions of Employment Act; Sectoral Determination 9 : the case of Sunflower retail store, Western Cape - Kukuta, Cebo (Stellenbosch : Stellenbosch University, 2019)
Thesis (MPA)--Stellenbosch University, 2019.